The mediating role of career satisfaction in the relationships between relationship quality, innovative work behavior and organizational trust - Sökmen, Alptekin; Sökmen, Alev; Kenek, Gökhan (Gazi Publishing, 2024)
The main purpose of this study is to determine the mediating role of career satisfaction in the relationship between relationship quality and innovative work behavior and organizational trust. 267 personnel working at the headquarters of a bank operating in Istanbul and service industry participated in the research. Within the scope of the research, data was collected by applying scales consisting of expressions related to variables to the relevant bank employees online and face to face. According to the analyses, there is a positive and significant relationship between all variables. In addition, as a result of the regression analyses, relationship quality has a significant effect on innovative work behavior, organizational trust and career satisfaction; It was concluded that career satisfaction also has a significant effect on organizational trust and innovative work behavior. The findings also show that career satisfaction has a partial mediating role between relationship quality, innovative work behavior and organizational trust.

İlişki kalitesinin, inovatif iş davranışı ve örgütsel güven ile ilişkisinde, kariyer tatmininin aracı rolünün tespiti bu çalışmanın temel amacıdır. Araştırmaya İstanbul’da hizmet sektöründe faaliyet gösteren bir bankanın genel merkezinde görev yapan 267 personel katılmıştır. Araştırma kapsamında, değişkenlere ilişkin ifadelerden oluşan ölçekler, ilgili banka çalışanlarına çevrimiçi ve yüz yüze uygulanarak veriler toplanmıştır. Yapılan analizlere göre tüm değişkenler arasında pozitif ve anlamlı bir ilişki bulunmaktadır. Ayrıca regresyon analizleri ile ilişki kalitesinin inovatif iş davranışı, örgütsel güven ve kariyer tatmini üzerinde anlamlı bir etkiye sahip olduğu; kariyer tatmininin de örgütsel güven ve inovatif iş davranışı üzerinde anlamlı bir etkiye sahip olduğu sonucuna ulaşılmıştır. Elde edilen bulgular, kariyer tatmininin, ilişki kalitesi ile inovatif iş davranışı arasında ve ilişki kalitesi ile örgütsel güven arasında kısmi aracılık rolüne sahip olduğunu da göstermektedir.
Keywords: Organisational Behaviour; ilişki kalitesi; inovatif iş davranışı; örgütsel güven; kariyer tatmini; hizmet sektörü; Örgütsel Davranış; Relationship Quality; Innovative Work Behavior; Organizational Trust; Career Satisfaction; Service Industry; 1. No poverty